Pengaruh Variasi Volume Pelarut Heksan dan Waktu Ekstraksi Terhadap Lemak Kakao yang Dihasilkan - Regina Resti Oktaviana; Lyse Bulo; Lydia Melawaty (Prodi Teknik Kimia, 2022)
Cocoa beans (theobroma cacao) are Indonesian agricultural commodities that have high economic value. Cocoa fat is one of cocoa bean processed products that is useful for aromatization. One method of extraction cocoa fat is the method of maceration, which is a separation method used to remove one or several components of a solid or liquid with the help of a solvent. In this research, cocoa fat extraction process is done, which is done percentage analysis, saponification number and acid number from cocoa fat extraction result. The purpose of this study was to determine the effect of process variables on cocoa fat content. Specifically include: (1) the effect of solvent volume on the amount of cocoa fat present, (2) to know the correlation of extraction time to the amount of cocoa fat produced. The results showed that the yield of cocoa fat was inversely proportional to the increase in the solvent volume variable (ml), and was directly proportional to the time of extraction (hours). The results showed that the highest percentage ofbrown oil of 18.12% was obtained from cocoa fat extraction using 200 ml hexane solvent for 6 hours yellow and solid and the aroma concentrated.